(Re)Animating Sociology of Suicide in Bangladesh - Rahman Khan, Anisur; Ratele, Kopano; Dery, Isaac (Italian Sociological Review, 2020)
Durkheim classic Le Suicide (1897) gave birth to ‘sociology of suicide’ and set down an influential theoretical and methodological framework to study the phenomenon. Its impact notwithstanding, the framework has received trenchant critiques as well as attracted modifications and revisions by many sociologists. Whilst the sociology of suicide appears not to attract large numbers of scholars in the global South, even though the magnitude of the problem is striking in some countries, we consider a way of (re)animating the area of study. To this end, we focus on Bangladesh as case study to think about as well as think with Durkheimian and post-Durkheimian propositions concerning sociology of suicide. Stated differently, we employ Bangladesh to work through some of the tenets, contestations, and revisions regarding suicide made by post-Durkheimian sociologists. Characterized by high rates of suicide, Bangladesh is an amply suitable case given the lack of any evidence of research envisioned under the framework of sociology of suicide. Taking off this we then make some suggestions regarding how sociologists in Bangladesh and more broadly the global South might (re)vitalize their methodological and epistemological work on suicide.